Assessing the Contribution of Agriculture for Boosting Nepalese Economy - Poudel, Omkar; Kharel, Khom Raj; Upadhyay, Yadav Mani (BMC Journal of Scientific Research, 2021)
Agriculture sector is the main components of economic development of developing countries likeNepal. This sector contributes boosting economy in terms of GDP, employment and food security,as more than 60% of Nepalese residents chose agriculture as their primary source of income. Theincrease in output and productivity in this sector is crucial for reducing poverty through long-term,high-growth economic growth. Increased agricultural production and output are important contrib-utors to the country's overall economic development. This study aims to look at how the agriculturesector contributes to the Nepalese economy's growth. Using data collected over a 20-year period,a simple linear regression model has applied to determine the economic impact of farm sector pro-duction on real GDP. The study finds a positive impact of agriculture sector on real GDP and othersectors. Though, agriculture sector has been facing diversified challenges improving its productionin Nepal.